The association between the triglyceride-glucose index with all-cause and cardiovascular mortality within the infertility population - Yuhan Wang; Yishu Tian; Feifei Zhou; Zixing Zhong (PLoS ONE, 2025)
Background The relationship between triglyceride-glucose (TyG) index and all-cause or cardiovascular mortality among infertile women remains unclear. In this study, we intended to utilize a national cohort from National Health and Nutrition Examination Survey (NHANES) to check the association between them. Methods Ten datasets from the NHANES database spanning almost 20 years were used as the data source and were combined within National Death Index for mortality follow-up. Multiple-variable Cox proportionate hazards regression models and three others were employed in this study to for assessing relationships among TyG index levels with all-cause and cardiovascular mortality. SPSS (version 29.0) and online websites were utilized for conducting the primary statistical analyses. Results 1,450 female participants were identified in this study. The samples were classified based on TyG index quartiles (7.05–11.95). The TyG index had a mean of 8.58±0.66. Participants with higher TyG indices were older-aged, had greater body mass index (BMI), and a stronger likelihood of having hypertension and diabetes (P < 0.05). Participants whose TyG indices were higher were older in age, along with increased BMI, and blood pressure along with diabetes (P < 0.05). Significant positive associations were observed among the TyG index and total mortality in the crude model (HR: 1.81, 95% CI: 1.27–2.58). Correlation persisted in Model 2 (following the adjustment of age and race) and Model 3 (following the adjustment of age, race, BMI, education, family poverty income ratio, smoking and drinking habits, menstrual regularity, hypertension, and diabetes). The TyG index did not affect the cardiovascular mortality in infertile women. Conclusion TyG index levels were in positive association with all-cause mortality within the female infertile population.